Basics of Italian Migration Policy - Kalantaryan, Edgar (YSU Journal of International Affairs, 2023)
In recent years, the problem of migration in the world has reached greater dimensions, which is caused by social, political, racial, military, as well as international economic crises. The main destination of migrants is the developed countries of the West, among which Italy is one of the most risky countries. Italy, until the 1970s of the previous century was a country of emigration. The opposite flow was also the result of the "open door policy" implemented in the country. Today, the management of that entire process is a serious challenge for the state, and the way to avoid it will be to revise the policy in that area and offer comprehensive solutions with specific legal regulations.